PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN KING TELUR ASIN - Dita Fitriasshinta; Tina Melinda (Journal of Management and Business Review, 2018)
Processed food from livestock products is common  in Indonesia. Besides meat, eggs can also be processed into a varian of dish and food. One of them is the result of egg processed innovation that has been existing for a long time is salted egg. Dity Global Nusantara is a company that produces and sells salted eggs with KING. It has been established since 2016, the company sells directly and cooperates through reseller. This research is doe in the purpose of finding out the influence of product quality and price on consumer satisfaction of  KING Salted Egg. This research uses quantitative method and multiple regression analysis model by involving KING Salted Egg consumer of  97 respondents as a sample then processed by using 23 SPSS. The result of this research that has been done states that product quality and price have positive influence  and significant on consumer satisfaction of KING Salted Egg.